The Precious Commodity of Time and Sub-Saharan Africa's Success in Keeping COVID-19 at Bay - Janet M. Wojcicki (Springer, 2020)
Most sub-Saharan African countries acted early and aggressively in response to the WHO COVID-19 warning by closing schools, international borders, limiting domestic travel and restricting large gatherings. The six most populous sub-Saharan African countries, at the beginning of July 2020 with the exception of Republic of South Africa, all had relatively modest COVID-19 case counts compared with European, North and South American and some Asian countries in spite of access to more limited medical resources and technologies. Shutdowns or shelter-in-places were put in place for 5 out of 6 countries surveyed well before the first reported COVID-19 death. Timely action to enact comprehensive public health measures are irreplaceable and cannot be substituted by later use of medical resources or technologies. In the case of Republic of South Africa, earlier and multiple instances of virus introduction may have made infection control much more difficult compared with other sub-Saharan African countries.